PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE ENTERPRISE ARCHITECTURE PLANNING (EAP) PADA KANTOR KETAHANAN PANGAN KABUPATEN SAROLANGUN - Tamala, David; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
Food Security is a organizer that assists policy, development, monitoring food availability, strengthening food distribution, establishing consumption patterns, monitoring market food security, and food administration. At present, in the Sarolangun District Food Security office, information system strategic planning has not yet been implemented such as CPCL receipts, distribution of production facilities, assistance and evaluation, financial management, human resource management and facilities and infrastructure management. Implementation is only carried out based on the needs of the vulnerability space which is limited to the interests of the agency without any overall planning and only for one particular function of the organization. The activities carried out in each of these fields are assisted by computers by using Microsoft Excel and Microsoft Word to process data as this results in information systems not being integrated between one field and another. With this, information system strategic planning is needed in the approach used is enterprise architecture planning. This study resulted in planning a form of blueprint regarding information organization in the form of enterprise architecture that can be used to support policy strategies in the development of an organized and integrated system in the Sarolangun District Food Security office